Breastfeeding and postnatal depression in Sabah, Malaysia - Mohamad Yusuff, Aza Sherin (Curtin University, 2013)
This is a cohort study of 2072 women in Sabah, Malaysia at an antenatal visit and followed up at 1, 3 and 6 months postpartum. The Edinburgh Postnatal Depression Scale was administered and details were obtained on infant feeding. 95.9%, 88.2% and 80.7% mothers were breastfeeding at each postpartum visit and the prevalence of depression was 13.8% at antenatal and 7.6%, 7.2% and 8% at 1 month, 3 months and 6 months postpartum, respectively.